2010
DOI: 10.1111/j.1365-2850.2010.01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Educational interventions in secondary education aiming to affect pupils' attitudes towards mental illness: a review of the literature

Abstract: Dealing with persons who have mental health problems is an issue that many people are likely to face with, whether they are health professionals or not. Positive attitudes towards people with mental illness play a major factor in their quality of life and social inclusion. Since adolescents will become active adult members of their communities in the near future, this paper reviews educational interventions in secondary education and how they aim to affect adolescent attitudes towards mental illness. Twelve st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The full search strategy is provided in the Appendix A. Additional data sources included reference lists of appropriate existing systematic literature reviews [29,30,[32][33][34][35][36]. The relevant references from these reviews were included in the data set.…”
Section: Search Strategymentioning
confidence: 99%
“…The full search strategy is provided in the Appendix A. Additional data sources included reference lists of appropriate existing systematic literature reviews [29,30,[32][33][34][35][36]. The relevant references from these reviews were included in the data set.…”
Section: Search Strategymentioning
confidence: 99%
“…12-15 However, there are also many initiatives, in the UK and other countries, taking anti-stigma programmes into the classroom (for example Rethink, Royal College of Psychiatrists). One review concluded that educational interventions in schools provide positive outcomes on pupils’ attitudes to mental illness, 16 a belief that seems widespread in the literature. However, it reports positive findings of the studies reviewed without clearly describing the quality of the studies, making the findings difficult to interpret.…”
mentioning
confidence: 99%
“…However, considering the grim situations young persons with ADHD and ASD end up in, evidenced in the present study, a general approach targeting students’ perceptions of mental illness should be considered. Educational interventions in secondary school targeting, e.g., the life situation for persons with ADHD and ASD could be a possible approach as such interventions may have a positive impact on attitudes and myths about mental illnesses (Sakellari, Leino-Kilpi, & Kalokerinou-Anagnostopoulou, 2011; Sakellari, Sourander, Kalokerinou-Anagnostopoulou, & Leino-Kilpi, 2014). Our study shows feelings of “stress and rest” and a span between these poles to which the young persons had to relate in everyday life was part of being vulnerable.…”
Section: Discussionmentioning
confidence: 99%